2018
DOI: 10.1007/s00373-018-1965-x
|View full text |Cite
|
Sign up to set email alerts
|

Total Equitable List Coloring

Abstract: An equitable coloring is a proper coloring of a graph such that the sizes of the color classes differ by at most one. A graph G is equitably k-colorable if there exists an equitable coloring of G which uses k colors, each one appearing on either ⌊|V (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In [12] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [24], series-parallel graphs [22], graphs with small maximum average degree [3], powers of cycles [9], and certain planar graphs (see [2], [13], [23], and [25]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [11]).…”
Section: Conjecture 3 ([12]) Every Graph G Is Equitablymentioning
confidence: 79%
See 1 more Smart Citation
“…In [12] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [24], series-parallel graphs [22], graphs with small maximum average degree [3], powers of cycles [9], and certain planar graphs (see [2], [13], [23], and [25]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [11]).…”
Section: Conjecture 3 ([12]) Every Graph G Is Equitablymentioning
confidence: 79%
“…It is also shown that this bound is tight for forests. Also, in [9], it is conjectured that if T is a total graph, then T is equitably k-choosable for each k ≥ max{χ ℓ (T ), ∆(T )/2+2} where χ ℓ (T ) is the smallest m such that T is m-choosable. In this note we will present some results on the equitable choosability of complete bipartite graphs that will give us equitable k-choosability for values of k that are smaller than the maximum degree of the graph.…”
Section: Conjecture 3 ([12]) Every Graph G Is Equitablymentioning
confidence: 99%
“…In [13] it is shown that Conjectures 3 and 4 hold for forests, complete bipartite graphs, connected interval graphs, and 2-degenerate graphs with maximum degree at least 5. Conjectures 3 and 4 have also been verified for outerplanar graphs [25], series-parallel graphs [23], graphs with small maximum average degree [3], certain graphs related to grids [4], powers of cycles [10], and certain planar graphs (see [2,14,24] and [26]). In 2013, Kierstead and Kostochka made substantial progress on Conjecture 3, and proved it for all graphs of maximum degree at most 7 (see [12]).…”
Section: Equitable Choosabilitymentioning
confidence: 90%
“…It is also shown that this bound is tight for forests. Also, in [10], it is conjectured that if T is a total graph, then T is equitably k-choosable for each k ≥ max{χ ℓ (T ), ∆(T )/2 + 2} where χ ℓ (T ) is the smallest m such that T is m-choosable. In this note we will present some results on the equitable choosability of complete bipartite graphs that will give us equitable k-choosability for values of k that are smaller than the maximum degree of the graph.…”
Section: Equitable Choosabilitymentioning
confidence: 99%
“…It is also shown that this bound is tight for forests. Also, in [8], it is conjectured that if T is a total graph, then T is equitably k-choosable for each k ≥ max{χ ℓ (T ), ∆(T )/2+2} where χ ℓ (T ), the list chromatic number of T , is the smallest m such that T is m-choosable. Finally, in [9], it is remarked that determining precisely which graphs are equitably 2-choosable is open.…”
Section: Equitable Choosabilitymentioning
confidence: 99%